2011
DOI: 10.1016/j.camwa.2011.06.057
|View full text |Cite
|
Sign up to set email alerts
|

A note on single-machine scheduling with general learning effect and past-sequence-dependent setup time

Abstract: a b s t r a c tIn this paper, we study a scheduling model with the consideration of both the learning effect and the setup time. Under the proposed model, the learning effect is a general function of the processing time of jobs already processed and its scheduled position, and the setup time is past-sequence-dependent. We then derive the optimal sequences for two single-machine problems, which are the makespan and the total completion time. Moreover, we showed that the weighted completion time, the maximum lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…For some single machine and a two-machine flowshop scheduling problems, they presented the optimal solution respectively. Lee [4] considered single-machine scheduling jobs with general learning effect and past-sequence-dependent setup time. For some single machine scheduling problems, they presented the optimal solution respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For some single machine and a two-machine flowshop scheduling problems, they presented the optimal solution respectively. Lee [4] considered single-machine scheduling jobs with general learning effect and past-sequence-dependent setup time. For some single machine scheduling problems, they presented the optimal solution respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Wang ve Li, [24]; Yin vd. [25]; Lee, [26] ile Bai v.d., [27] geçmiş sıra bağımlı hazırlık zamanlı ve farklı öğrenme etkili durumda ele almışlar.…”
Section: Introductionunclassified
“…They also show that the total weighted completion time minimization problem and the maximum tardiness minimization problem can be solved in polynomial time under certain conditions. Lee [9] considered the learning effect and setup time, a scheduling model has been considered. It has been shown that the proposed model for two single machines can be solved in polynomial time for problems with objective function processing time, total completion time minimization.…”
mentioning
confidence: 99%